Novel thermal analysis model of the foot-shoe sole interface during gait motion - Shimazaki, Y.; Aisaka, K. (Proceedings, 2018)
Excessive heat at the foot-shoe sole interface negatively affects a human`s thermal comfort. An understanding of the thermal behavior at this interface is important for alleviating this discomfort. During gait motion, a human`s body weight cyclically compresses a shoe sole (commonly constructed of viscoelastic materials), generating heat during loading. To evaluate the thermal effects of this internal heat generation on foot comfort, we developed and empirically validated a thermal analysis model during gait motion. A simple, one-dimensional prediction model for heat conduction with heat generation during compressive loading was used. Heat generation was estimated as a function of the shoe sole`s material properties (e.g., elastic modulus) and various gait parameters. When compared with experimental results, the proposed model proved effective in predicting thermal behavior at the foot-shoe sole interface under various conditions and shows potential for improving a human`s thermal comfort during gait motion through informed footwear design.